- Home
- Study Guides
A logarithm is the inverse function to an exponential function. It is defined as the exponent to which a fixed base must be raised to yield a given number.
There is actually a simple way to solve difficult questions that involve logarithmic or exponential equations. The key is to remember that an exponential equation is just a special case of a logarithmic equation, so it’s possible to convert an exponential equation into a logarithmic equation. So how do we convert the equation?
${{a}^{b}}=c\underset{{}}{\longleftrightarrow}b={{\log }_{a}}c$
$a$: base
$b$: index
Important Notes:
${{\log }_{10}}x=\lg x$
${{\log }_{e}}x=\ln x$
Convert each of the following to logarithmic form.
(a)
${{x}^{2y}}=4$
(a) ${{x}^{2y}}=4$
(b)
${{5}^{x}}=12$
(b) ${{5}^{x}}=12$
(c)
${{\left( 4x \right)}^{5-p}}=a$
(c) ${{\left( 4x \right)}^{5-p}}=a$
$\begin{aligned}
{{x}^{2y}}&=4 \\
& \Downarrow \\
2y&={{\log }_{x}}4
\end{aligned}$
$\begin{aligned}
{{5}^{x}}&=12 \\
& \Downarrow \\
x&={{\log }_{5}}12
\end{aligned}$
$\begin{aligned}
{{\left( 4x \right)}^{5-p}}&=a \\
& \Downarrow \\
5-p&={{\log }_{4x}}a
\end{aligned}$
$\begin{aligned}
{{x}^{2y}}&=4 \\
& \Downarrow \\
2y&={{\log }_{x}}4
\end{aligned}$
$\begin{aligned}
{{5}^{x}}&=12 \\
& \Downarrow \\
x&={{\log }_{5}}12
\end{aligned}$
$\begin{aligned}
{{\left( 4x \right)}^{5-p}}&=a \\
& \Downarrow \\
5-p&={{\log }_{4x}}a
\end{aligned}$
Solve each of the following equations.
(a)
$\ln 4x=5$
(a) $\ln 4x=5$
(b)
${{\log }_{x}}16=4$
(b) ${{\log }_{x}}16=4$
(c)
$\ln (3x)=6$
(c) $\ln (3x)=6$
(d)
${{\log }_{k}}81=2$
(d) ${{\log }_{k}}81=2$
$\begin{aligned}
\ln 4x&=5 \\
{{\log }_{\text{e}}}4x&=5 \\
4x&={{\text{e}}^{5}} \\
x&=\frac{1}{4}{{\text{e}}^{5}}
\end{aligned}$
$\begin{aligned}
{{\log }_{x}}16&=4 \\
{{x}^{4}}&=16 \\
x&=\pm \sqrt[4]{16} \\
x&=2\,\,\text{or}\,\,-2
\end{aligned}$
$x=-2$ (rej, as $x>0$)
$\therefore x=2$
$\begin{aligned}
\ln \left( 3x \right)&=6 \\
{{\log }_{\text{e}}}\left( 3x \right)&=6 \\
{{\text{e}}^{6}}&=3x \\
x&=\frac{1}{3}{{\text{e}}^{6}}
\end{aligned}$
$\begin{aligned}
{{\log }_{k}}81&=2 \\
{{k}^{2}}&=81 \\
k&=\pm \sqrt{81} \\
& =9\,\,\text{or}-9
\end{aligned}$
$k=-9$ (rej, as $k>0$)
$\therefore k=9$
$\begin{aligned}
\ln 4x&=5 \\
{{\log }_{\text{e}}}4x&=5 \\
4x&={{\text{e}}^{5}} \\
x&=\frac{1}{4}{{\text{e}}^{5}}
\end{aligned}$
$\begin{aligned}
{{\log }_{x}}16&=4 \\
{{x}^{4}}&=16 \\
x&=\pm \sqrt[4]{16} \\
x&=2\,\,\text{or}\,\,-2
\end{aligned}$
$x=-2$ (rej, as $x>0$)
$\therefore x=2$
$\begin{aligned}
\ln \left( 3x \right)&=6 \\
{{\log }_{\text{e}}}\left( 3x \right)&=6 \\
{{\text{e}}^{6}}&=3x \\
x&=\frac{1}{3}{{\text{e}}^{6}}
\end{aligned}$
$\begin{aligned}
{{\log }_{k}}81&=2 \\
{{k}^{2}}&=81 \\
k&=\pm \sqrt{81} \\
& =9\,\,\text{or}-9
\end{aligned}$
$k=-9$ (rej, as $k>0$)
$\therefore k=9$
The logarithm of $1$ to the any base will always yield $0$.
${{\log }_{a}}1=0$
e.g.
${{\log }_{5}}1=0$ | ${{\log }_{17.5}}1=0$ | $\ln 1=0$ |
The logarithm of any number to the same base will always yield $1$.
${{\log }_{a}}a=1$
e.g.
${{\log }_{11}}11=1$ | ${{\log }_{20.5}}20.5=1$ | $\ln e=1$ |
The product law for logarithms can be applied to simplify a logarithm of a product of many terms. The product law for logarithms states that the sum of the logs of two numbers is equal to the log of the product of two numbers.
${{\log }_{a}}b+{{\log }_{a}}c={{\log }_{a}}\left( b\times c \right)$
Important Notes:
$\ln 2+\ln5=\ln10$
${{\log }_{3}}2+{{\log }_{3}}20={{\log }_{3}}40$
${{\log }_{2}}3+{{\log }_{2}}7+{{\log }_{2}}2={{\log }_{2}}42$
Simplify ${{\lg }_{6}}2+{{\lg }_{6}}3$ if possible.
$\begin{aligned}
& {{\lg }_{6}}2+{{\lg }_{6}}3 \\
& ={{\log }_{6}}\left( 2\times 3 \right) \\
& ={{\log }_{6}}6 \\
& =1 \\
\end{aligned}$
The quotient law for logarithms is also often used when simplifying logs. The quotient law for logarithms states that the difference between the logs of two numbers is equal to the log of the quotient of two numbers.
${{\log }_{a}}b-{{\log }_{a}}c={{\log }_{a}}\left( \frac{b}{c} \right)$
Important Notes:
$\ln 2-\ln5=\ln\frac{2}{5}$
${{\log }_{3}}2-{{\log }_{3}}20={{\log }_{3}}\frac{1}{10}$
${{\log }_{2}}16-{{\log }_{2}}5+{{\log }_{2}}2={{\log }_{2}}\frac{16\times 2}{5}$
Simplify ${{\log }_{5}}25-{{\log }_{5}}5$ if possible.
$\begin{aligned}
& {{\log }_{5}}25-{{\log }_{5}}5 \\
& ={{\log }_{5}}\left( \frac{25}{5} \right) \\
& ={{\log }_{5}}5 \\
& =1 \\
\end{aligned}$
The power law for logarithms can be applied for expanding or simplifying logarithms. The power law of logarithms allows us to move the exponent to the front of the logarithm if the logarithmic term has an exponent.
${{\log }_{a}}{{b}^{r}}=r{{\log }_{a}}b$
Important Notes:
${{\left( {{\log }_{a}}x \right)}^{3}}\ne 3{{\log }_{a}}x$
But ${{\left( {{\log }_{a}}x \right)}^{3}}=\left( {{\log }_{a}}x \right)\left( {{\log }_{a}}x \right)\left( {{\log }_{a}}x \right)$
${{\log }_{2}}{{5}^{x}}=x{{\log }_{2}}5$
${{\log }_{3}}\sqrt{2}=\frac{1}{2}{{\log }_{3}}2$
Evaluate each of the following without using the calculator.
(a)
${{\log }_{8}}64$
(a) ${{\log }_{8}}64$
(b)
${{\log }_{2}}\sqrt{4}+{{\log }_{2}}\sqrt{3}-{{\log }_{2}}\sqrt{6}$
(b) ${{\log }_{2}}\sqrt{4}+{{\log }_{2}}\sqrt{3}-{{\log }_{2}}\sqrt{6}$
$\begin{aligned}
{{\log }_{8}}64&={{\log }_{8}}{{8}^{2}} \\
& =2{{\log }_{8}}8 \\
& =2\left( 1 \right) \\
& =2
\end{aligned}$
$\begin{aligned}
& {{\log }_{2}}\sqrt{4}+{{\log }_{2}}\sqrt{3}-{{\log }_{2}}\sqrt{6} \\
& ={{\log }_{2}}\left( \sqrt{4}\cdot \sqrt{3} \right)-{{\log }_{2}}\sqrt{6} \\
& ={{\log }_{2}}\frac{\sqrt{4}\cdot \sqrt{3}}{\sqrt{6}} \\
& ={{\log }_{2}}\sqrt{\frac{4\cdot 3}{6}} \\
& ={{\log }_{2}}\sqrt{2} \\
& ={{\log }_{2}}{{2}^{\frac{1}{2}}} \\
& =\frac{1}{2}{{\log }_{2}}2 \\
& =\frac{1}{2} \\
\end{aligned}$
$\begin{aligned}
{{\log }_{8}}64&={{\log }_{8}}{{8}^{2}} \\
& =2{{\log }_{8}}8 \\
& =2\left( 1 \right) \\
& =2
\end{aligned}$
$\begin{aligned}
& {{\log }_{2}}\sqrt{4}+{{\log }_{2}}\sqrt{3}-{{\log }_{2}}\sqrt{6} \\
& ={{\log }_{2}}\left( \sqrt{4}\cdot \sqrt{3} \right)-{{\log }_{2}}\sqrt{6} \\
& ={{\log }_{2}}\frac{\sqrt{4}\cdot \sqrt{3}}{\sqrt{6}} \\
& ={{\log }_{2}}\sqrt{\frac{4\cdot 3}{6}} \\
& ={{\log }_{2}}\sqrt{2} \\
& ={{\log }_{2}}{{2}^{\frac{1}{2}}} \\
& =\frac{1}{2}{{\log }_{2}}2 \\
& =\frac{1}{2} \\
\end{aligned}$
From the previous section, we know that the common logarithm is also called the “logarithm with a base of $10$,” and the natural logarithm is referred to as the “logarithm with a base of $\text{e}$”. Although both logarithms are commonly called the logarithm, they are actually two separate calculations. Most graphing calculators have keys that allow you to work with logarithms: LOG for common logarithms and LN for natural logarithms.
What happens if we have questions involving logarithms with a base other than $10$ and $\text{e}$? The change-of-base formula allows us to convert any logarithm into another logarithm with a different base, which can be very useful in solving certain types of questions.
${{\log }_{a}}b=\frac{{{\log }_{c}}b}{{{\log }_{c}}a}$
Important Notes:
${{\log }_{x}}y=\frac{1}{{{\log }_{y}}x}$
Converting the logarithm into another logarithm with base $7$:
${{\log }_{2}}5=\frac{{{\log }_{7}}5}{{{\log }_{7}}2}$
Converting the logarithm into another logarithm with base $p$:
${{\log }_{11}}2=\frac{{{\log }_{p}}2}{{{\log }_{p}}11}$
(a)
Given that $p={{\log }_{a}}9$, find ${{\log }_{3}}a$ in terms of $p$.
(a) Given that $p={{\log }_{a}}9$, find ${{\log }_{3}}a$ in terms of $p$.
(b)
If $p=\lg 14$, ${{\log }_{14}}1\frac{2}{5}$ in terms of $p$.
(b) If $p=\lg 14$, ${{\log }_{14}}1\frac{2}{5}$ in terms of $p$.
$\begin{aligned}
p&={{\log }_{a}}9 \\
p&=\frac{{{\log }_{3}}9}{{{\log }_{3}}a} \\
{{\log }_{3}}a&=\frac{{{\log }_{3}}{{3}^{2}}}{p} \\
& =\frac{2{{\log }_{3}}3}{p} \\
& =\frac{2}{p}
\end{aligned}$
$\begin{aligned}
p&=\lg 14\\&={{\log }_{10}}14\\&=\frac{{{\log }_{14}}14}{{{\log }_{14}}10}\\&=\frac{1}{{{\log }_{14}}10} \\
{{\log }_{14}}10&=\frac{1}{p}
\end{aligned}$
$\begin{aligned}
& {{\log }_{14}}\left( 1\frac{2}{5} \right)\\&={{\log }_{14}}\left( \frac{7}{5} \right) \\
& ={{\log }_{14}}\left( \frac{7\cdot 2}{5\cdot 2} \right) \\
& ={{\log }_{14}}\left( \frac{14}{10} \right) \\
& ={{\log }_{14}}14-{{\log }_{14}}10 \\
& =1-\frac{1}{p}
\end{aligned}$
$\begin{aligned}
p&={{\log }_{a}}9 \\
p&=\frac{{{\log }_{3}}9}{{{\log }_{3}}a} \\
{{\log }_{3}}a&=\frac{{{\log }_{3}}{{3}^{2}}}{p} \\
& =\frac{2{{\log }_{3}}3}{p} \\
& =\frac{2}{p}
\end{aligned}$
$\begin{aligned}
p&=\lg 14\\&={{\log }_{10}}14\\&=\frac{{{\log }_{14}}14}{{{\log }_{14}}10}\\&=\frac{1}{{{\log }_{14}}10} \\
{{\log }_{14}}10&=\frac{1}{p}
\end{aligned}$
$\begin{aligned}
& {{\log }_{14}}\left( 1\frac{2}{5} \right)\\&={{\log }_{14}}\left( \frac{7}{5} \right) \\
& ={{\log }_{14}}\left( \frac{7\cdot 2}{5\cdot 2} \right) \\
& ={{\log }_{14}}\left( \frac{14}{10} \right) \\
& ={{\log }_{14}}14-{{\log }_{14}}10 \\
& =1-\frac{1}{p}
\end{aligned}$
Suppose we have a system of equations that contains multiple logarithmic equations and multiple unknown variables, how do we address them? In this section, we will learn how to solve systems of logarithmic equations by substitution.
Solve the simultaneous equations.
$\begin{aligned}
{{\log }_{4}}x-{{\log }_{2}}y&=2 \\
{{3}^{x}}&=81\left( {{9}^{\frac{3}{2}-3y}} \right)
\end{aligned}$
$\begin{aligned}
{{\log }_{4}}x-{{\log }_{2}}y&=2—(1) \\
{{3}^{x}}&=81\left( {{9}^{\frac{3}{2}-3y}} \right)—(2)
\end{aligned}$
From (2):
$\begin{aligned}
{{3}^{x}}&={{3}^{4}}\left( {{\left( {{3}^{2}} \right)}^{\frac{3}{2}-3y}} \right) \\
{{3}^{x}}&={{3}^{4}}\cdot {{3}^{3-6y}} \\
{{3}^{x}}&={{3}^{4+3-6y}} \\
x&=4+3-6y \\
x&=7-6y—(3)
\end{aligned}$
Substitute (3) into (1):
$\begin{aligned}
{{\log }_{4}}\left( 7-6y \right)-{{\log }_{2}}y&=2 \\
\frac{{{\log }_{2}}\left( 7-6y \right)}{{{\log }_{2}}{{2}^{2}}}-{{\log }_{2}}y&=2 \\
\frac{{{\log }_{2}}\left( 7-6y \right)}{2}-{{\log }_{2}}y&=2 \\
{{\log }_{2}}\left( 7-6y \right)-2{{\log }_{2}}y&=4 \\
{{\log }_{2}}\left( 7-6y \right)-{{\log }_{2}}{{y}^{2}}&=4 \\
{{\log }_{2}}\frac{7-6y}{{{y}^{2}}}&=4 \\
\frac{7-6y}{{{y}^{2}}}&={{2}^{4}} \\
7-6y&=16{{y}^{2}} \\
16{{y}^{2}}+6y-7&=0\\
\left( 2y-1 \right)\left( 8y+7 \right)&=0 \\
y&=\frac{1}{2}\,\,\text{or}\,\,-\frac{7}{8}
\end{aligned}$
$y=-\frac{7}{8}$ (rej, as ${{\log }_{2}}\left( -\frac{7}{8} \right)$ is undefined)
Substitute $y=\frac{1}{2}$ into (3):
$\begin{aligned}
x&=7-6\left( \frac{1}{2} \right) \\
& =4
\end{aligned}$
$\therefore y=\frac{1}{2},\,\,x=4$
The logarithm is a very common and useful way to measure the relative magnitudes of things. Here are a few examples of logarithms in real-life:
The mass, $m$ grams, of a radioactive substance, present at time t days after first being observed, is given by the formula $m=28{{e}^{-0.00072t}}$.
(a)
Find the value of $m$ when $t=20$.
(a) Find the value of $m$ when $t=20$.
(b)
Find the value of $t$ when the mass is half of its value at $t=0$.
(b) Find the value of $t$ when the mass is half of its value at $t=0$.
(c)
State the value which $m$ approaches as $t$ becomes very large.
(c) State the value which $m$ approaches as $t$ becomes very large.
(d)
Sketch the graph of $m$ against $t$.
(d) Sketch the graph of $m$ against $t$.
When $t=20$,
$\begin{aligned}
m&=28{{\text{e}}^{-0.00072\left( 20 \right)}} \\
& =27.5996 \\
& =27.6\,\text{grams }\left( 3\,\,\text{s}\text{.f}\text{.} \right)
\end{aligned}$
When $t=0$,
$\begin{aligned}
m&=28{{\text{e}}^{-0.00072\left( 0 \right)}} \\
& =28{{\text{e}}^{0}} \\
& =28\,\text{grams}
\end{aligned}$
New $m=\frac{28}{2}=14$
$\begin{aligned}
m&=28{{\text{e}}^{-0.00072t}} \\
14&=28{{\text{e}}^{-0.00072t}} \\
\frac{1}{2}&={{\text{e}}^{-0.00072t}} \\
\ln \frac{1}{2}&=\ln {{\text{e}}^{-0.00072t}} \\
\ln \frac{1}{2}&=-0.00072t \\
t&=\frac{\ln \frac{1}{2}}{-0.00072} \\
& =962.7 \\
& =963\,\,\text{days}\,\left( 3\,\,\text{s}\text{.f}\text{.} \right)
\end{aligned}$
$t\to \infty ,m\to 0$
$m$ approaches $0$ gram.
When $t=20$,
$\begin{aligned}
m&=28{{\text{e}}^{-0.00072\left( 20 \right)}} \\
& =27.5996 \\
& =27.6\,\text{grams }\left( 3\,\,\text{s}\text{.f}\text{.} \right)
\end{aligned}$
When $t=0$,
$\begin{aligned}
m&=28{{\text{e}}^{-0.00072\left( 0 \right)}} \\
& =28{{\text{e}}^{0}} \\
& =28\,\text{grams}
\end{aligned}$
New $m=\frac{28}{2}=14$
$\begin{aligned}
m&=28{{\text{e}}^{-0.00072t}} \\
14&=28{{\text{e}}^{-0.00072t}} \\
\frac{1}{2}&={{\text{e}}^{-0.00072t}} \\
\ln \frac{1}{2}&=\ln {{\text{e}}^{-0.00072t}} \\
\ln \frac{1}{2}&=-0.00072t \\
t&=\frac{\ln \frac{1}{2}}{-0.00072} \\
& =962.7 \\
& =963\,\,\text{days}\,\left( 3\,\,\text{s}\text{.f}\text{.} \right)
\end{aligned}$
$t\to \infty ,m\to 0$
$m$ approaches $0$ gram.
Do sign up for our Free Mini-Courses and try our well-structured curriculum to see how it can help to maximize your learning in mathematics online.
Secondary School Additional Mathematics Free Online Course Sign Up.
You may also find the pricing and plans for our Additional Mathematics unlimited all-access courses here!
With our online courses, you can learn at your own pace and take your time whenever it’s most convenient for you. Experience learning with us now for free!
Topics included:
How can we help?